1965
DOI: 10.1039/tf9656101425
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of mixtures of acetone and hexafluoroacetone. Combination reactions of methyl and trifluoromethyl radicals

Abstract: The photolysis of mixtures of acetone and hexafluoroacetone has been studied in the range 23-240°C. In addition to C2H6, C2F6 and CH3CF3, the products also contained CH2 = CF2.The following reactions are therefore proposed :Reaction (5) as not previously been observed. Defining $* by q5* = kla/k$k$, $* = (2.0f0.2) exp (170f80)/RT. These results indicate that Ela = E2 = E3 4.The product of reaction (la) is a "hot" molecule which can be stabilized to CH3CF3 by collisions. The ratio R C H~C F~/ R C H~= C F~ is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

1966
1966
1978
1978

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 10 publications
5
36
0
Order By: Relevance
“…The combining radicals in this case were 2CH2F. Giles and Whittle (2) demonstrated that such a process also occurs in the combination of methyl and trifluoromethyl radicals, and showed that the combination occurs with zero activation energy to give an activated trifluoroethane molecule (CH,CF,?) which may decompose to give difluoroethylene and H F or may be stabilized by collision…”
Section: Introductionmentioning
confidence: 99%
“…The combining radicals in this case were 2CH2F. Giles and Whittle (2) demonstrated that such a process also occurs in the combination of methyl and trifluoromethyl radicals, and showed that the combination occurs with zero activation energy to give an activated trifluoroethane molecule (CH,CF,?) which may decompose to give difluoroethylene and H F or may be stabilized by collision…”
Section: Introductionmentioning
confidence: 99%
“…The respective collision numbers at 400 ' I< for CF3, C2F5, and C3F7 are 7.5 X 1013, 1.1 X 1014, and 1.3 X 1014 rnole-l cc s-l (u,,, = 4.0 A, uc2,: = 5.5 A, ucari = 6.5 A). Very recent work (11) indicates that Ez = 0 for CF3 con~bination, so that we may equate El -$E2 with El as an absolute value. In the C3F7 + ethane system, allowance was made for this from a knowledge of the C4H10 (R + R R2) and the C3F7C2H5 formed (12), but the value of El was not affected whether the correction was made or not, although the reason for this is not apparent (13).…”
Section: Results Hhtd Discussionmentioning
confidence: 99%
“…I n combination reactions of unlike radicals, ratio [I] would be temperature independent even if the same barrier existed for the three reactions. A small barrier for such reactions (not over 1.5 kcal/mole) has been suggested for such combinations (7,8) but very recent worl; on cross colnbination of CI-13 and CF3 (9,10) indicates no temperature dependence.…”
Section: Ti-\ble Imentioning
confidence: 99%